P0318HYPERKALEMIA: EPIDEMIOLOGY AND MANAGEMENT. (6th June 2020) - Felah, Eya; Samia, Barbouch; Mariem, Hajji; Ben amor, Shedha; Chargui, Soumaya; Amiri, Mohamed lotfi; Trabelsi, Raja; Goucha, Rym; Ben Hmida, Fethi; Ounissi, Mondher; Ben abdallah, Taieb
Abstract: Background and Aims: Hyperkalemia is a dreadful biological event that can immediately compromise the vital prognosis. Etiologies are many and varied. The aim of our study is to better characterize the epidemiological and clinical aspects of this disorder in order to establish adequate diagnostic and therapeutic strategies in order to intervene effectively and in the shortest possible time. Methods: Cross-sectional study carried out over a period of 12 months [January-December 2017] including all emergency calls for hyperkalemia greater than 5.5 mmol / l and undergoing hemodialysis in the nephrology department. Results: We collected 185 patients (Sex ratio= 1.43) aged on average 61.8 ± 16.1 years [18-94 years]. 70.3% had serum potassium between 5.5 and 7 mmol / l and 29.7% greater than 7. Patients mainly came from emergencies in 71.4% of cases. Main symptoms consisted in oligoanuria, vomiting, chest pain, and febrile syndrome in 38.9%, 10.8%, %, and 5.9% of cases, respectively. Of these patients, 76.2% are known to be chronic renal failure whose 29.7% are in chronic dialysis. Acute renal failure (ARF) was diagnosed in 30.3% of patients. Of these, 39.4% were functional AKI, 41% were obstructive and organic AKI in 19.6% of cases. Mean serum potassium was 6.7 ± 0.9mmol / l [5.5-11] associated with metabolic acidosis in 52.4% of cases. Mean serum creatinine was 988umol /l[184-3270]. The electrical signs of hyperkalemia were noted in 40% (n = 74) of patients: large T in 28.6% of cases, atrioventricular block (AVB) in 3.8% of cases including a 3rd BAV degree in 1.6% of cases, QRS wide in 11.4% of cases and sinus bradycardia in 7% of cases, Ventricular Extrasystoles and a branch block found respectively in 3.2% of cases. 30.8% (n = 57) of the patients were under hyperkalaemic treatment. In fact, 27 % of patients took a blocker of the renin-angiotensin system, 7% were on aldoactone, 13.5% of patients on þetabloquant, 1.6 % of whom were on kaleoride and / or admitted to intensive care and infused with KCl. Medical treatment was started urgently in 42.7 % of cases and included the administration of twenty ml 10% ca gluconate that was given intravenously over 5-10minutes, insulin with glucose, sodium polystyrene sulfate (Kayexalete) and salbutamol, sodium bicarbonate indicated for severe metabolic acidosis (pH<7.20). Overall mortality was 21.1% of cases . Conclusion: Hyperkalemia remains a frequent metabolic disorder. Renal failure and acidosis were the main factors associated to hyperkalemia in our study. The clinical and therapeutic subtleties must be known by any caregiver in order to effectively mitigate the harmful effects of this disorder, mainly in the cardiac function.